2018
DOI: 10.3892/etm.2018.6094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexmedetomidine, midazolam, and propofol on lipopolysaccharide‑stimulated dendritic cells

Abstract: Abstract. Dexmedetomidine, midazolam and propofol are common sedative drugs used in the intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…In the present study however, we generated a dose response curve for DEX, ranging from 0.01 to 10 µM and identified a concentration of 1 µM to be the least cytotoxic. As this concentration is generally used in the clinic 39 , our data thus endorse it to be potentially safer in humans. Data presented in this study are also consistent with earlier work completed by Wu et al which demonstrated that DEX protected neurons against apoptosis, axonal degradation, and synaptic degeneration after traumatic brain injury in a murine model 28 .…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In the present study however, we generated a dose response curve for DEX, ranging from 0.01 to 10 µM and identified a concentration of 1 µM to be the least cytotoxic. As this concentration is generally used in the clinic 39 , our data thus endorse it to be potentially safer in humans. Data presented in this study are also consistent with earlier work completed by Wu et al which demonstrated that DEX protected neurons against apoptosis, axonal degradation, and synaptic degeneration after traumatic brain injury in a murine model 28 .…”
Section: Discussionsupporting
confidence: 56%
“…To avoid confounders of the whole animal or intact brain slices, we used a well-established in vitro cell culture model 33 . 1 to 2.5 μM has been recommended as a clinically relevant DEX concentration for in vitro experiments, and 5 μM deemed to be a higher dose in the clinical domain 39 . In the present study, we tested for the first time, all of the above concentrations to obtain a more comprehensive dose–response curve.…”
Section: Resultsmentioning
confidence: 99%
“…Deep sedation is thought to arise at plasma concentrations above 1.9 ng/mL [48,48]. Another study reported that 0.1, 1, and 10 μM of dexmedetomidine are high concentrations for clinical use, and 0.001 μM of dexmedetomidine is the lowest concentration for clinical use [50]. Therefore, the concentration of dexmedetomidine used in this study fall within the concentration range used in the clinics.…”
Section: Discussionmentioning
confidence: 55%
“…Leukotrienes are comprised a class of vital cytokines that can accelerate the growth of human cancer cells [ 20 , 21 ]. Propofol exerts an anticancer affect by altering the function of dendritic cells [ 22 ] and has been reported to prevent the proliferation and metastasis of multiple cancers. For example, propofol was shown to prevent the progress of pancreatic cancer under hypoxic conditions via ADAM8 [ 23 ] and affect the proliferation and apoptosis of cardia cancer cells via the MAPK/ERK signaling pathway [ 24 ].…”
Section: Discussionmentioning
confidence: 99%